The crusades : A history - Riley-Smith, Jonathan (Continuum, 2005)
The Crusades: A History is a comprehensive, single-volume history of the Crusades, from their beginnings in the eleventh century through to their decline and eventual ending at the close of the eighteenth century. As well as providing an account of the major Crusades, the book describes the organization of a Crusade, the experience of crusading and the Crusaders themselves.In a new preface and afterword, Jonathan Riley-Smith surveys recent developments in the field and examines responses to the Crusades in different periods, from the Romantics to the Islamic world today. The book concludes with a challenge to a historiographical tradition that has often been fraught with controversy.